Practise healthy social media habits - Ng, Alvin Lai Oon * (Star Media Group Berhad, 2020)
Studies have shown how unpleasant emotions can spread like wildfire on social media, and mental health academics are calling for something to be done before it gets out of hand. Sunway University Department of Psychology head and professor Dr Alvin Ng (pic) said several techniques can be utilised to manage social media consumption and reduce its negative impact including cleaning up your newsfeed.